New Evidence of Generational Progress for Mexican Americans - Brian Duncan; Jeff Grogger; Ana Sofia Leon; Stephen Trejo (Institute of Labor Economics (IZA), 2019)
U.S.-born Mexican Americans suffer a large schooling deficit relative to other Americans, and standard data sources suggest that this deficit does not shrink between the 2nd and later generations. Standard data sources lack information on grandparentsâ exteuro™ countries of birth, however, which creates potentially serious issues for tracking the progress of later-generation Mexican Americans. Exploiting unique NLSY97 data that address these measurement issues, we find substantial educational progress between the 2nd and 3rd generations for a recent cohort of Mexican Americans. Such progress is obscured when we instead mimic the limitations inherent in standard data sources. Similar patterns emerge for cognitive test scores and for annual earnings.
Keywords: J15; J61; J62; 330; assimilation; generational progress; Mexican Americans